Relationship between systemic immune-inflammation index and depression among individuals with and without cardiovascular disease - Dan Liu; Chaojie He; Xinguo Luo (Journal of Cardiothoracic Surgery)
Abstract Objective Depression is a common comorbidity in cardiovascular disease (CVD), and both conditions are associated with chronic inflammation. The systemic immune-inflammation index (SII) has emerged as a promising marker of systemic inflammation, but its role in association with depressive symptoms, particularly in the context of CVD, remains unclear. This study aims to investigate the association of SII with depressive symptoms in individuals with and without CVD using cross-sectional data from NHANES (2005–2016). Methods A total of 29,479 participants from the National Health and Nutrition Examination Survey (NHANES) 2005–2016 waves were included. Depressive symptoms were assessed through Patient’s Health Questionnaire (PHQ-9). SII was calculated as the platelet count × neutrophil count/lymphocyte count. In order to determine the relationships between SII and depressive symptoms in participants with and without CVD, binary logistic regression model and smooth curve fitting were used. We also performed sensitivity analyses and subgroup analysis. Results The total prevalence of depressive symptoms was 8.73% among the 29,479 participants analyzed. After adjusting for confounding factors, a higher SII was significantly associated with increased depressive symptoms in the total population (OR per SD increase: 1.101, 95% CI: 1.060–1.144, P < 0.0001). This association was stronger in participants without CVD (OR: 1.121, 95% CI: 1.073–1.172, P < 0.0001) compared to those with CVD (OR: 1.055, 95% CI: 0.973–1.144, P = 0.19571). Participants in the highest SII tertile had a significantly higher risk of depressive symptoms compared to those in the lowest tertile, particularly in the non-CVD group (OR: 1.161, 95% CI: 1.026–1.313, P = 0.01765). Conclusion The SII is independently associated with an increased risk of depressive symptoms, particularly in individuals without CVD. These findings suggest that the SII may serve as a valuable predictor of depressive symptoms in the general population, with potential implications for early screening and intervention strategies. Further research is needed to elucidate the mechanisms underlying this association and to explore the clinical utility of SII in depressive symptoms assessment, especially in the context of cardiovascular health.